Evolution of the Malaysian halal certification system : viable system model as the diagnostic framework - Khairul Akmaliah Adham,; Alina Abdul Rahim,; Nur Sa’adah Muhamad,; Adlin Masood,; Mohd Fuaad Said, (Penerbit Universiti Kebangsaan Malaysia, 2022)
As a Muslim-majority country, Malaysia has a responsibility to fulfil the needs of Muslim citizens to practise their religion. Therefore, the Malaysian halal certification system needs to be viable, that is, to be self-sufficient within its environment. The extant literature has explained the elements of viable systems but placed less emphasis on how systems develop into viability. This study aims to bridge this gap by using the Viable System Model to diagnose the globally recognised Malaysian halal certification system as the system-in-focus. This qualitative study gathered data mainly from interviews with 20 executives from relevant institutions with direct involvement in the system’s implementation. The findings of the study provide insights into the development milestones of a system with elements of viability. Among others, this development was found to happen in stages that are marked by crises and corresponding actions by the respective authorities. Suggestions for the system’s viability are provided.